2020
DOI: 10.1097/md.0000000000019714
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological risk factors in the light of the revised 2018 International Federation of Gynecology and Obstetrics staging system for early cervical cancer with staging IB

Abstract: To validate the revised 2018 International Federation of Gynecology and Obstetrics (FIGO) staging system for cervical cancer on the survival of patients who underwent radical hysterectomy for 2009 FIGO stage IB carcinomas. We retrospectively identified and reviewed 251 patients treated with radical hysterectomy for 2009 FIGO stage IB cervical carcinomas from January 2011 to December 2016. The re-staged IB cohort consisted of 2018 FIGO stage IB1 (tumor size <2 cm), IB2 (2–3.9 cm), IB3 (≥4 cm), and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…In this particular study, restaging using the FIGO 2018 staging system revealed an estimated 13% and 28% stage migration for Stage IB3 and Stage IIIC, respectively [ 11 ]. In an analysis of 251 cervical cancer patients conducted by Zeng et al, restaging the patients using the 2018 FIGO system resulted in an 11.2% and 7.2% stage migration for Stage IB3 and Stage IIIC, respectively [ 12 ]. Grigsby et al reported that 53% of patients had stage migration when the FIGO 2018 system was used [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this particular study, restaging using the FIGO 2018 staging system revealed an estimated 13% and 28% stage migration for Stage IB3 and Stage IIIC, respectively [ 11 ]. In an analysis of 251 cervical cancer patients conducted by Zeng et al, restaging the patients using the 2018 FIGO system resulted in an 11.2% and 7.2% stage migration for Stage IB3 and Stage IIIC, respectively [ 12 ]. Grigsby et al reported that 53% of patients had stage migration when the FIGO 2018 system was used [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previously mentioned Yan et al analysis found the FIGO 2018 stage to be an independent prognostic factor for OS [ 12 ]. In the Zeng et al study mentioned before, the five-year progression-free survival rates showed the same trend with increasing stage reflecting upon the revised 2018 FIGO staging system's effectiveness in predicting outcomes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node status is one of the important prognostic factors in early-stage cervical cancer patients underwent RHPL [4,7]. The DFS and OS were significantly different between the patients with and without MLN [18,19]. The number of MLN is associated with survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty patients with cervical cancer with lymph node metastases who received radiotherapy at Liaoning Cancer Hospital and Institute from May 2019 to November 2020 were selected and their data retrospectively analyzed. According to the 2018 International Federation of Gynecology and Obstetrics (FIGO) staging criteria for cervical cancer, all patients were staged as IIIC1r, IIIC2r, IVA, and IVB with lymph node metastases, and were pathologically diagnosed with squamous cell carcinoma, adenocarcinoma, and others 4 . A short diameter >8 mm was consistent with metastatic lymph nodes according to imaging data from patients before treatment: a total of 78 lymph nodes were included in the study 5 .…”
Section: Methodsmentioning
confidence: 99%